2006
DOI: 10.1186/1471-2202-7-52
|View full text |Cite
|
Sign up to set email alerts
|

Delay aversion but preference for large and rare rewards in two choice tasks: implications for the measurement of self-control parameters

Abstract: Background: Impulsivity is defined as intolerance/aversion to waiting for reward. In intoleranceto-delay (ID) protocols, animals must choose between small/soon (SS) versus large/late (LL) rewards. In the probabilistic discount (PD) protocols, animals are faced with choice between small/ sure (SS) versus large/luck-linked (LLL) rewards. It has been suggested that PD protocols also measure impulsivity, however, a clear dissociation has been reported between delay and probability discounting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 46 publications
5
48
0
Order By: Relevance
“…However, there is evidence that these types of decisions may, in fact, be dissociable. Intact rats differentially alter their preference for larger rewards associated with increasing delays or risk (Adriani and Laviola, 2006). After extended training, rats shift to choosing a small/immediate reward vs a larger/ delayed reward as the delay increases.…”
Section: Mechanisms Underlying Changes In Risky Choice Induced By Da mentioning
confidence: 99%
“…However, there is evidence that these types of decisions may, in fact, be dissociable. Intact rats differentially alter their preference for larger rewards associated with increasing delays or risk (Adriani and Laviola, 2006). After extended training, rats shift to choosing a small/immediate reward vs a larger/ delayed reward as the delay increases.…”
Section: Mechanisms Underlying Changes In Risky Choice Induced By Da mentioning
confidence: 99%
“…However, recent studies have cast a doubt on the hypothetical equivalence of a decrease in probability to an increase in delay; specifically, several studies reported that parameters in delay and probability discounting functions are not so strongly correlated as originally supposed [13,20], and some studies have reported that neurobiological/psychopharmacological manipulation distinctly impacts delay and probability discounting [3,21]. Additionally, a recent study by Bickel's group has proposed an analytical strategy combining delay and probability [22].…”
Section: Introductionmentioning
confidence: 99%
“…standing over the partner lying with its back on the floor. Laviola, 2006). Hence, animals had to make a choice between a small/sure (SS) or a large/luck-linked (LLL) reward (session length 25 min ; timeout 15 s ; see Supplementary Material for more details).…”
Section: Expt 1 : Social-interaction Testmentioning
confidence: 99%
“…Rats underwent a Probabilistic-delivery operant task, specifically tailored to induce a kind of 'temptation ' to gamble on the possibility of a rare but bigger prize over the certainty of a lower one (Adriani & Laviola, 2006). Control and Sil rats shifted to the latter option, as expected (Adriani et al 2009).…”
Section: Repertoire Of Gambling-like Traitsmentioning
confidence: 99%